Flood hazard zonation using remote sensing, geographic information system, and analytic hierarchy process in the Bhagirathi River Basin, Uttarakhand, India - Aditya Kumar Varma; Anurag Dhote; Aneesh Mathew; Chinthu Naresh; Padala Raja Shekar (Results in Earth Sciences)
Floods are seen as a substantial environmental hazard. A flood hazard map is a crucial tool for evaluating regions vulnerable to flooding. This study seeks to identify flood-prone regions along the Bhagirathi River in the Uttarkashi and Tehri Garhwal districts of Uttarakhand. A hybrid approach utilizing remote sensing (RS) and geographic information system (GIS), in conjunction with the Analytical Hierarchy (AHP) Process, was implemented to delineate flood hazard zones within the study area. Seven parameters were selected for this purpose: drainage density, precipitation, slope, land use/land cover (LULC), distance from the river, soil type, and topographic wetness index (TWI). The thematic maps of the parameters were reclassified after ranks were assigned to different classes. AHP was employed to construct a pairwise comparison matrix for all parameters to ascertain the relative weight of each parameter. A weighted overlay analysis was performed by combining reclassified thematic layers with their respective AHP-derived weights to generate the flood hazard map (FHM) for the study area. The output is divided into five distinct flooding hazard zones: very high, high, moderate, low, and very low. The precision of these classifications was confirmed using the Receiver Operating Characteristic Curve (ROC) and Area Under the Curve (AUC). The findings revealed that the accuracy rate for AHP was 66.8 %. The study's findings can serve as a convenient resource to aid in the management and reduction of rescue operations on the banks of the Bhagirathi.